Industries without smokestacks: Telecommunication and ICT-based services trade - Cláudio R. Frischtak (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper provides a basic understanding of the nature of emerging key information and communication technologies, and establishes the distance of countries from high-quality access to the internet - the necessary threshold one needs to cross in order to make use of such technologies. The paper underlines the importance of governments creating a more open and competitive environment to attract infrastructure investment (in terms of fibre-optic rings and cable links, among others), and foster rivalry among suppliers of devices and mainly services, thereby benefiting users with lower prices and better-quality services so as to steer societies away from being marginalized by the information and communication technology revolution.
Keywords: L86; L96; O10; O33; 330; economic development; innovation; least developed country; technological change; growth